Bacillus amyloliquefaciens Confers Tolerance to Various Abiotic Stresses and Modulates Plant Response to Phytohormones through Osmoprotection and Gene Expression Regulation in Rice - Tiwari, Shalini; Prasad, Vivek; Chauhan, Puneet S.; Lata, Charu (Frontiers in Plant Science, 2017)
Being sessile in nature, plants have to withstand various adverse environmental stress conditions including both biotic and abiotic stresses. Comparatively, abiotic stresses such as drought, salinity, high temperature and cold pose major threat to agriculture by negatively impacting plant growth and yield worldwide. Rice is one of the most widely consumed staple cereals across the globe, the production and productivity of which is also severely affected by different abiotic stresses. Therefore, several crop improvement programs are directed towards developing stress tolerant rice cultivars either through marker assisted breeding or transgenic technology. Alternatively, some known rhizospheric competent bacteria are also known to improve plant growth during abiotic stresses. A plant growth promoting rhizobacteria (PGPR), Bacillus amyloliquefaciens NBRI-SN13 (SN13) was previously reported by our lab to confer salt stress tolerance to rice seedlings. However, the present study investigates the role of SN13 in ameliorating various abiotic stresses such as salt, drought, desiccation, heat, cold, and freezing on a popular rice cv. Saryu-52 under hydroponic growth conditions. Apart from this, seedlings were also exogenously supplied with abscisic acid (ABA), salicylic acid (SA), jasmonic acid (JA) and ethephon (ET) to study the role of SN13 in phytohormone-induced stress tolerance as well as its role in abiotic and biotic stress cross-talk. All abiotic stresses and phytohormone treatments significantly affected various physiological and biochemical parameters like membrane integrity and osmolyte accumulation. SN13 also positively modulated stress-responsive gene expressions under various abiotic stresses and phytohormone treatments suggesting its multifaceted role in cross-talk among stresses and phytohormones in response to PGPR. To the best of our knowledge, this is the first report on detailed analysis of plant growth promotion and stress alleviation by a PGPR in rice seedlings subjected to various abiotic stresses and phytohormone treatments for 0, 1, 3, 10 and 24 h.